Position dependent mass Scarf Hamiltonians generated via the Riccati equation. (21st May 2018) - Cruz y Cruz, S; Santiago‐Cruz, C
Abstract : The construction of position dependent mass Scarf Hamiltonians of the trigonometric as well as the hyperbolic types is addressed by means of the factorization method and the Riccati equation. These Hamiltonians are shown to be independent of the ordering parameter of the kinetic term. Additionally, new families of Hamiltonians with the Scarf spectrum are also determined by supersymmetry. Some examples for masses with and without singularities are considered to illustrate our results.